Addition of telephone coaching to a physiotherapist-delivered physical activity program in people with knee osteoarthritis: A randomised controlled trial protocol - Bennell, Kim L (BioMed Central, 2012)
BACKGROUND: Knee osteoarthritis (OA) is one of the most common and costly chronic musculoskeletal conditions world-wide and is associated with substantial pain and disability. Many people with knee OA also experience co-morbidities that further add to the OA burden. Uptake of and adherence to physical activity recommendations is suboptimal in this patient population, leading to poorer OA outcomes and greater impact of associated co-morbidities. This pragmatic randomised controlled trial will investigate the clinical- and cost-effectiveness of adding telephone coaching to a physiotherapist-delivered physical activity intervention for people with knee OA. METHODS/DESIGN: 168 people with clinically diagnosed knee OA will be recruited from the community in metropolitan and regional areas and randomly allocated to physiotherapy only, or physiotherapy plus nurse-delivered telephone coaching. Physiotherapy involves five treatment sessions over 6 months, incorporating a home exercise program of 4–6 exercises (targeting knee extensor and hip abductor strength) and advice to increase daily physical activity. Telephone coaching comprises 6–12 telephone calls over 6 months by health practitioners trained in applying the Health Change Australia (HCA) Model of Health Change to provide behaviour change support. The telephone coaching intervention aims to maximise adherence to the physiotherapy program, as well as facilitate increased levels of participation in general physical activity. The primary outcomes are pain measured by an 11-point numeric rating scale and self-reported physical function measured by the Western Ontario and McMaster Universities Osteoarthritis Index subscale after 6 months. Secondary outcomes include physical activity levels, quality-of-life, and potential moderators and mediators of outcomes including self-efficacy, pain coping and depression. Relative cost-effectiveness will be determined from health service usage and outcome data. Follow-up assessments will also occur at 12 and 18 months. DISCUSSION: The findings will help determine whether the addition of telephone coaching sessions can improve sustainability of outcomes from a physiotherapist-delivered physical activity intervention in people with knee OA. TRIAL REGISTRATION: Australian New Zealand Clinical Trials Registry reference: ACTRN12612000308897